Scheduling optimization using local search and genetic algorithm - Koblasa, F. (2008)
This paper presents possible ways to improve enterprises’ scheduling, simplified as Job-Shop Scheduling Problem, using heuristics. It describes proceedings through Local Search and Genetic Algorithm and includes examples of Single Swap Local Search and Genetic Algorithm with Random Keys representation and chromosome correction. The paper also includes a comparison of makespan improvements existing in the Local Search and in the Genetic Algorithm.